The Frequency of Communication Between the Synovial Compartments of the Equine Temporomandibular Joint: A Contrast-Enhanced Computed Tomographic Assessment - Pimentel, Karen L.; Carmalt, James L. (Frontiers in Veterinary Science, 2021)
Background: There is conflicting evidence regarding communication between the two compartments of the equine temporomandibular joint (TMJ). Understanding the inter-relationship between TMJ compartments is critical for diagnostic and clinical management purposes. Objective: To determine the frequency of communication between the discotemporal joint (DTJ) and the discomandibular joint (DMJ) of the equine TMJ in horses free of overt disease. Study design: A randomized, blinded, controlled cadaveric study. Methods: Equine cadaver heads (n = 20), with no reported history of potential TMJ disease, were collected and stored frozen until use. Horses were randomized to treatment group, such that Group A horses (n = 10) underwent arthrocentesis of the left DTJ and the right DMJ compartments, while Group B (n = 10) underwent arthrocentesis of the left DMJ and the right DTJ compartments of the TMJ, for a total of 40 joints. Computed tomography (CT) imaging was performed before, and after, intra-articular injection of contrast media in each head. Two observers, blinded to treatment group, independently interpreted CT images. Results: Communication between synovial compartments occurred in the left TMJ of two horses. Arthroscopic evaluation revealed that both horses had a perforation of the intra-articular disc in the region of the caudomedial fibrous expansion. Mild anterior displacement of the abnormal disc in the joint of one horse was demonstrated using magnetic resonance imaging (MRI). Main limitations: Sample size, the use of owner-provided animals’ history and frozen specimens. Conclusions: No physiological communication was present between DTJ and the DMJ in the equine TMJ of the cases studied, regardless of which compartment underwent arthrocentesis. Two joints had pathological communications. These results suggest that diagnostic, and medical, treatment of intra-articular disease may be most effective when both joint compartments are injected. Furthermore, this study illustrates the value of contrast enhancement while imaging the equine TMJ.